Reason and Faith in the Geology of the 19th Century: In the second centenary of William Buckland’s «Vinditiae Geologiae» (1820) - Prieto Santana, María Dolores (Razón y fe, 2020)
200 years ago, in 1820, Vinditiae Geologiae was published, written by the Reverend William Buckland (1784-1856), a brief and ardent manifesto of the history of science, in the line of Theology of Nature. It was trying to confirm the Genesis account with the Geology data. It was hotly debated in its time and this debate spurred the emergence of modern geology. Thanks to this, the nineteenth century is thus the true “paradigm” of modern geology. It already acquires the status of “formalized science” with the ability to have a unified body of doctrine assumed by the scientific community, a rationality of its own, ability to develop its own hypotheses and maintain a scientific methodology based on principles. The figures of Charles Lyell and Charles Robert Darwin were decisive for the construction of a Geology not dependent on religious ideas.
Keywords: Buckland; geology; diluvism; philosophy of science; Lyell; Hutton; Darwin; science and religion